Twin-crane scheduling using ATCRSS approach - Fan, Xiaoxuan (2015)
Yard crane operations efficiency affects the operations of the entire container terminal. Twin cranes system is introduced to improve the operations efficiency of the yard cranes. The yard crane scheduling problem is NP-hard, and twin crane scheduling problem is even harder. As such, an effective heuristic is required to produce optimal job sequences within reasonable amount of time. The ATCRSS index rule is adapted to the twin crane scheduling problem. Modifications are made on the ATCRSS index in order to better deal with the twin cranes scheduling problem. The modification includes: 1) modifying ATCRSS setup time; 2) introducing tardiness term for ATCRSS index calculation; 3) introducing lookahead in the scheduling process. Simulation function is also adapted for the twin cranes system. The job sequences processing function is revamped to process one job sequence from each of the two cranes, and the decongestion function is added to the simulation in order to handle inter-crane interference. Experiments are carried out to test and compare the performance of the abovementioned modifications. From the experiment results, the modification on the setup time and tardiness term alone cannot produce better performance than the original ATCRSS index. However, the hybrid of lookahead and non-lookahead algorithms can significantly improve the scheduling performance.